Porous alumina ceramic preparation and surface pore sealing method
By adopting the double -peak particle size powder ratio and nanopolymium aluminum -soluble gel sealing technology, the problem of high sintering temperature of porous aluminum oxide matrix is difficult to control density, and realizes high -performance multi -porous aluminum ceramics at a lower temperature. And improve its hydrophobicity.
Patent Information
- Application Number
- CN202411476320.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing preparation methods for porous alumina matrix include high sintering temperature, difficult to control density, and immature surface sealing technology, making it difficult to effectively improve the hydrophobicity of composite materials.
Using double-peak particle size powder ratio, that is, the mix of small-particle size oxide powder (10-200nm) and large-particle size oxide powder (100-1000Nm), combined with the mixture of aluminum alumina solidar and alumina powder with aluminum powder, Perform vacuum immersion treatment to form a uniform seal layer to improve hydrophobicity.
High-performance porous alumina ceramics are prepared at lower temperatures, which control the porosity and mechanical properties of the material, improve the hydrophobicity of the material, and extend the service life of the composite material.
Smart Images

Figure CN119350058A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic material preparation, and in particular relates to a method for preparing porous alumina ceramics and sealing the surfaces thereof. Background Art
[0002] The new generation of aircraft engines relies on advanced materials, processes and innovative structures. Traditional high-temperature alloys are difficult to meet the needs of high-thrust engines due to their high density and limited temperature rise space. Continuous fiber reinforced ceramic matrix composites (CFCCs) overcome the brittleness of traditional ceramics and have the advantages of high modulus, high hardness, high strength, corrosion resistance, high temperature stability and low density, becoming a promising material for engine hot end applications. CFCCs are mainly composed of fibers, matrix and interface phases. The selection of different fibers and matrices can significantly affect the performance of composites, and the fiber / matrix interface is also crucial in determining mechanical properties and fracture behavior. Too high a density means that the interface is tightly bonded, limiting the reinforcement mechanism; too low a density hinders load transfer and reduces toughness.
[0003] The porous matrix can effectively deflect cracks without the need for fiber surface coating, has a simple manufacturing process, and is suitable for ceramic-based composites. Among them, alumina has become a widely used oxide matrix due to its high mechanical properties, high temperature stability, high melting point, good dielectric properties and oxidation resistance. α-Al2O3 avoids phase change at high temperatures, ensuring performance consistency. However, above 1200°C, the fibers are prone to creep, affecting the mechanical properties. In addition, at normal pressure and 1200°C, a single alumina powder is difficult to achieve the required composite density requirements (70-80%). Therefore, the preparation of high-performance porous alumina ceramics at lower temperatures is a key challenge in the development of aerospace composites. Summary of the invention
[0004] The purpose of the present invention is to solve the problems existing in the current preparation method of porous alumina matrix, such as high sintering temperature, difficult to control density, immature surface sealing technology, and difficulty in effectively improving the hydrophobicity of the composite material, and to provide a method for preparing and surface sealing a porous alumina ceramic.
[0005] The method for preparing porous alumina ceramics and sealing the surface of the ceramics is implemented according to the following steps:
[0006] 1. Mixing a small-particle aluminum oxide powder having a particle size of 10-200 nm and a large-particle aluminum oxide powder having a particle size of 100-1000 nm in a mass ratio of (90-96):(4-10) to obtain a mixed powder;
[0007] 2. Forming the mixed powder to obtain a green body;
[0008] 3. Sintering the green body at a temperature of 1100-1250° C. for 2-6 hours to obtain a porous alumina matrix;
[0009] 4. mixing the nano-alumina sol with the added alumina powder to obtain a mixed slurry;
[0010] 5. Immersing the porous alumina substrate into the mixed slurry for vacuum impregnation treatment to obtain an impregnated alumina substrate;
[0011] 6. Drying the impregnated alumina substrate to obtain a dried substrate;
[0012] 7. Heat-treating the dried substrate at a temperature of 1100-1250° C. to complete the sealed alumina ceramic substrate;
[0013] The mass fraction of the nano-alumina sol in the mixed slurry in step 4 is 90wt% to 95wt%, and the mass fraction of the added alumina powder is 5wt% to 10wt%.
[0014] The present invention provides a method for preparing and surface sealing porous alumina ceramics. In the process of preparing porous alumina ceramics, the present invention innovatively adopts a bimodal particle size powder ratio, that is, a mixture of small-particle size alumina powder (particle size is 10-200nm) and large-particle size alumina powder (particle size is 100-1000nm). This ratio can form a more uniform pore structure during the sintering process, while reducing the sintering temperature, so that the porosity and performance of the material are optimally balanced. The large-particle size powder can partially play the role of a pore former during the sintering process, and can accurately control the number, size and distribution of pores. The small-particle size powder plays multiple roles such as filling voids, improving fluidity, improving the overall performance and consistency of the material, and reducing performance fluctuations and defects. This unique powder ratio method enables the present invention to prepare high-performance porous alumina ceramics at a lower temperature, avoiding the performance degradation of the fiber at high temperatures.
[0015] In terms of surface sealing, the present invention uses a mixed slurry formed by mixing nano-alumina sol and added alumina powder for vacuum impregnation treatment. The sol particles in the nano-alumina sol are attracted to the surface of the ceramic substrate by electrostatic force, thereby adhering to and forming a thin film. As the sol particles continue to accumulate, they begin to fill the pores on the surface of the substrate, thereby forming a dense and uniform sealing layer. As the temperature rises, the sol particles undergo an Ostwald ripening process, that is, smaller particles dissolve and re-precipitate onto larger particles, thereby further densifying the sealing layer, effectively sealing the surface pores, and improving the hydrophobicity of the material. This innovative nano-alumina sol sealing technology not only improves the hydrophobicity of porous alumina ceramics, but also prevents internal fibers from contacting the outside world, thereby extending the service life of the composite material.
[0016] The method for preparing porous alumina ceramics and sealing the surface of the porous alumina ceramics of the present invention has the following beneficial effects:
[0017] (1) The present invention prepares high-performance porous alumina ceramics by using optimized bimodal particle size powder and sintering process. The sintering temperature is relatively low, which avoids the performance degradation of the fiber at high temperature.
[0018] (2) The present invention can adjust the porosity and mechanical properties of the porous alumina matrix to achieve an optimal balance by controlling the addition amount of large-particle alumina powder and the sintering temperature. The porosity of the porous alumina matrix increases with the increase in the addition amount of large-particle alumina powder and decreases with the increase in the sintering temperature.
[0019] (3) The present invention effectively seals the surface pores through the penetration of nano-alumina sol to form a uniform sealing layer, thereby improving the hydrophobicity and preventing the internal fibers from contacting the outside world, thereby extending the service life of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a surface morphology of the porous alumina ceramic without surface sealing prepared in Example 1;
[0021] Figure 2 This is a cross-sectional morphology of the porous alumina ceramic after surface sealing prepared in Example 1;
[0022] Figure 3 This is a cross-sectional morphology of the porous alumina ceramic after surface sealing prepared in Example 2;
[0023] Figure 4 This is a cross-sectional morphology of the porous alumina ceramic after surface sealing prepared in Example 3;
[0024] Figure 5 This is a cross-sectional morphology of the alumina fiber reinforced alumina composite ceramic prepared in Example 4;
[0025] Figure 6 This is a cross-sectional morphology of the graphene-enhanced alumina composite ceramic prepared in Example 5;
[0026] Figure 7 This is a surface morphology of the porous alumina ceramic without surface sealing prepared in the comparative example. DETAILED DESCRIPTION
[0027] Specific implementation method 1: The method for preparing porous alumina ceramics and sealing the surface of the porous alumina ceramics in this implementation method is implemented according to the following steps:
[0028] 1. Mixing a small-particle aluminum oxide powder having a particle size of 10-200 nm and a large-particle aluminum oxide powder having a particle size of 100-1000 nm in a mass ratio of (90-96):(4-10) to obtain a mixed powder;
[0029] 2. Forming the mixed powder to obtain a green body;
[0030] 3. Sintering the green body at a temperature of 1100-1250° C. for 2-6 hours to obtain a porous alumina matrix;
[0031] 4. mixing the nano-alumina sol with the added alumina powder to obtain a mixed slurry;
[0032] 5. Immersing the porous alumina substrate into the mixed slurry for vacuum impregnation treatment to obtain an impregnated alumina substrate;
[0033] 6. Drying the impregnated alumina substrate to obtain a dried substrate;
[0034] 7. Heat-treating the dried substrate at a temperature of 1100-1250° C. to complete the sealed alumina ceramic substrate;
[0035] The mass fraction of the nano-alumina sol in the mixed slurry in step 4 is 90wt% to 95wt%, and the mass fraction of the added alumina powder is 5wt% to 10wt%.
[0036] In step 1 of this embodiment, the particle size of the large-particle alumina powder is preferably 400-800 nm.
[0037] The porous alumina ceramic preparation and surface sealing method of this embodiment can prepare porous ceramics with different porosities at a relatively low temperature, and the hydrophobicity of the matrix is effectively improved by the surface sealing treatment, thus providing a new method for the preparation of high-performance porous alumina ceramic materials.
[0038] This embodiment adopts a bimodal particle size powder ratio, that is, a mixture of small-particle size alumina powder and large-particle size alumina powder. This ratio can form a more uniform pore structure during the sintering process, while reducing the sintering temperature, so that the porosity and performance of the material are optimally balanced. The large-particle size powder can partially play the role of a pore former during the sintering process, and can control the number, size and distribution of pores. The small-particle size powder plays multiple roles such as filling voids, improving fluidity, improving the overall performance and consistency of the material, and reducing performance fluctuations and defects. Nano-alumina sol sealing is also another important aspect. This surface sealing method is to immerse the ceramic substrate in nano-alumina sol instead of injecting it. It effectively seals the surface pores by forming a uniform dense layer on the surface of the porous alumina substrate, thereby improving the hydrophobicity of the material.
[0039] The method for preparing porous alumina ceramics in this embodiment includes a series of process flows such as powder mixing, molding, sintering, and nano-alumina sol sealing, especially the key step of sintering the porous alumina ceramic matrix after impregnation with nano-alumina sol to complete the sealing. From the perspective of performance and application, the porous alumina ceramics prepared in this embodiment focus on the dual advantages of its porous structure and surface hydrophobicity, and can be more suitable for scenes requiring high performance and special properties such as aerospace and high-temperature structural materials.
[0040] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the mixing method in step 1 adopts dry mixing or wet mixing.
[0041] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that in step one, small-particle alumina powder with a particle size of 10-200nm and large-particle alumina powder with a particle size of 100-1000nm are mixed in a mass ratio of (90-96): (4-10), and then graphene is added, and anhydrous ethanol is added to perform ball milling under an argon atmosphere, and a mixed powder is obtained after drying; wherein the graphene accounts for 1.2 to 2.0wt% of the total mass of the small-particle alumina powder and the large-particle alumina powder.
[0042] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that the molding method in step 2 adopts dry pressing molding or suction filtration molding.
[0043] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the preparation method of the blank is replaced by:
[0044] 1. Mixing a small-size alumina powder with a particle size of 10-200 nm and a large-size alumina powder with a particle size of 100-1000 nm in a mass ratio of (90-96):(4-10), adding deionized water for wet ball milling to obtain an alumina slurry;
[0045] 2. Inject the alumina slurry of step 1 into the stacked alumina fibers for vacuum impregnation, and then dry them to complete the grouting and impregnation treatment. Repeat the grouting and impregnation treatment multiple times to obtain a green body.
[0046] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that the alumina particle size in the nano alumina sol in step 4 is 30-70nm, and the mass fraction is 10wt%-30wt%.
[0047] Specific embodiment 7: This embodiment is different from any one of specific embodiments 1 to 6 in that the particle size of the added aluminum oxide powder in step 4 is 10-200 nm.
[0048] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the temperature of the drying treatment in step six is 50-100° C. and the drying time is 10-24 hours.
[0049] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that the heat treatment time in step 7 is 2-6 hours.
[0050] Specific implementation method ten: This implementation method is different from specific implementation methods one to nine in that the alumina ceramic substrate after sealing is subjected to hydrophobic treatment.
[0051] Specific embodiment eleven: The difference between this embodiment and specific embodiment ten is that the hydrophobic treatment is to immerse the sealed alumina ceramic substrate in a methanol solution with a mass fraction of 1wt%-5wt% of tridecafluorooctyltriethoxysilane for 1-4h, and dry it in an oven at 100-200℃.
[0052] Example 1: The method for preparing porous alumina ceramics and sealing the surface of the porous alumina ceramics in this example is implemented according to the following steps:
[0053] 1. A small-size alumina powder with a particle size of 200 nm and a large-size alumina powder with a particle size of 600 nm were mixed in a mass ratio of 94:6, and anhydrous ethanol was added for wet ball milling to obtain a mixed powder;
[0054] 2. Filtering the mixed powder to obtain a green body;
[0055] 3. Sintering the green body at 1200° C. for 2 hours to obtain a porous alumina matrix;
[0056] 4. Mixing the nano-alumina sol (the alumina particle size in the sol is 50 nm and the mass fraction is 15 wt%) with the external alumina powder with a particle size of 200 nm to obtain a mixed slurry;
[0057] 5. Immersing the porous alumina substrate into the mixed slurry for vacuum impregnation treatment to obtain an impregnated alumina substrate;
[0058] 6. Drying the impregnated alumina substrate at 60° C. for 12 hours to obtain a dried substrate;
[0059] 7. Heat treating the dried substrate at 1200° C. for 2 hours to complete the sealed alumina ceramic substrate;
[0060] 8. The sealed alumina ceramic substrate was immersed in a methanol solution containing 1 wt% of tridecafluorooctyltriethoxysilane for hydrophobic treatment for 1 hour, and finally dried in an oven at 140° C. for 1 hour to complete the hydrophobic treatment;
[0061] The mass fraction of the nano-alumina sol in the mixed slurry in step 4 is 94wt%, and the mass fraction of the added alumina powder is 6wt%.
[0062] The porous alumina matrix obtained in step 3 of this embodiment has a density of 74%, a compressive strength of 522 MPa, a wetting angle with water of 71°, and a pore diameter of about 66 nm in pressure pump pore analysis. The surface morphology is as follows Figure 1 The wetting angle between the porous alumina ceramics obtained in step 7 and water is 101°, and the cross-sectional morphology is as follows: Figure 2 As shown, the sealing layer thickness is 19.2 μm. The wetting angle between the porous alumina ceramic obtained in step eight and water is 140°. The porous alumina ceramic obtained in this embodiment meets the density requirement of the porous matrix of the composite material of 70%-80%, has good compression resistance, and the surface sealing is successful.
[0063] Example 2: The method for preparing porous alumina ceramics and sealing the surface of the porous alumina ceramics in this example is implemented according to the following steps:
[0064] 1. A small-size alumina powder with a particle size of 200 nm and a large-size alumina powder with a particle size of 600 nm were mixed in a mass ratio of 92:8, and anhydrous ethanol was added for wet ball milling to obtain a mixed powder;
[0065] 2. Filtering the mixed powder to obtain a green body;
[0066] 3. Sintering the green body at 1200° C. for 2 hours to obtain a porous alumina matrix;
[0067] 4. Mixing the nano-alumina sol (the alumina particle size in the sol is 50 nm and the mass fraction is 15 wt%) with the external alumina powder with a particle size of 200 nm to obtain a mixed slurry;
[0068] 5. Immersing the porous alumina substrate into the mixed slurry for vacuum impregnation treatment to obtain an impregnated alumina substrate;
[0069] 6. Drying the impregnated alumina substrate at 60° C. for 12 hours to obtain a dried substrate;
[0070] 7. Heat treating the dried substrate at 1200° C. for 2 hours to complete the sealed alumina ceramic substrate;
[0071] The mass fraction of the nano-alumina sol in the mixed slurry in step 4 is 90wt%, and the mass fraction of the added alumina powder is 10wt%.
[0072] The porous alumina matrix obtained in step 3 of this embodiment has a density of 72%, a compressive strength of 496 MPa, a wetting angle with water of 68°, and a pore diameter of about 69 nm in the pressure pump pore analysis. The porous alumina ceramic obtained in step 7 has a wetting angle with water of 95° and a cross-sectional morphology as shown in FIG. Figure 3 As shown, the sealing layer thickness is 38.1 μm. The porous alumina ceramics obtained in this embodiment meet the density requirement of the porous matrix of the composite material in the range of 70%-80%, have good compression resistance, and the surface pores are successfully sealed.
[0073] Example 3: The preparation and surface sealing method of porous alumina ceramics in this example is implemented according to the following steps:
[0074] 1. A small-size alumina powder with a particle size of 200 nm and a large-size alumina powder with a particle size of 600 nm were mixed in a mass ratio of 96:4, and anhydrous ethanol was added for wet ball milling to obtain a mixed powder;
[0075] 2. Filtering the mixed powder to obtain a green body;
[0076] 3. Sintering the green body at 1200° C. for 2 hours to obtain a porous alumina matrix;
[0077] 4. Mixing the nano-alumina sol (the alumina particle size in the sol is 50 nm and the mass fraction is 15 wt%) with the external alumina powder with a particle size of 200 nm to obtain a mixed slurry;
[0078] 5. Immersing the porous alumina substrate into the mixed slurry for vacuum impregnation treatment to obtain an impregnated alumina substrate;
[0079] 6. Drying the impregnated alumina substrate at 60° C. for 12 hours to obtain a dried substrate;
[0080] 7. Heat treating the dried substrate at 1200° C. for 2 hours to complete the sealed alumina ceramic substrate;
[0081] The mass fraction of the nano-alumina sol in the mixed slurry in step 4 is 92wt%, and the mass fraction of the added alumina powder is 8wt%.
[0082] The porous alumina matrix obtained in step 3 of this embodiment has a density of 76%, a compressive strength of 554 MPa, a wetting angle with water of 74°, and a pore diameter of about 63 nm in the pressure pump pore analysis. The porous alumina ceramic obtained in step 7 has a wetting angle with water of 108° and a cross-sectional morphology as shown in FIG. Figure 4As shown, the sealing layer thickness is 25.2 μm. The porous alumina ceramics obtained in this embodiment meet the density requirement of the porous matrix of the composite material in the range of 70%-80%, have good compression resistance, and the surface pores are successfully sealed.
[0083] Embodiment 4: The preparation and surface sealing method of alumina fiber reinforced alumina composite ceramics in this embodiment is implemented according to the following steps:
[0084] 1. Alumina powder with a small particle size of 200 nm and alumina powder with a large particle size of 600 nm were mixed in a mass ratio of 90:10, and deionized water was added for wet ball milling to obtain an alumina slurry;
[0085] 2. Injecting alumina slurry into the stacked alumina fibers for vacuum impregnation, followed by drying to complete the grouting and impregnation process, and repeating the grouting and impregnation process multiple times to obtain a green body;
[0086] 3. Sintering the green body at a temperature of 1200° C. for 1 hour to obtain an alumina fiber reinforced alumina composite ceramic, hereinafter referred to as composite ceramic;
[0087] 4. Mixing the nano-alumina sol (the alumina particle size in the sol is 50 nm and the mass fraction is 15 wt%) with the external alumina powder with a particle size of 200 nm to obtain a mixed slurry;
[0088] 5. Immersing the composite ceramic into the mixed slurry for vacuum impregnation treatment to obtain the impregnated composite ceramic;
[0089] 6. Drying the impregnated composite ceramic at 60° C. for 12 hours to obtain a dried composite ceramic;
[0090] 7. Heat treating the dried composite ceramic at a temperature of 1200° C. for 2 hours to complete the sealed composite ceramic;
[0091] The mass fraction of the nano-alumina sol in the mixed slurry in step 4 is 92wt%, and the mass fraction of the added alumina powder is 8wt%.
[0092] The alumina fiber reinforced alumina composite ceramic obtained in step 3 of this embodiment has a density of 78%, a compressive strength of 680 MPa, a wetting angle with water of 76°, and a pore diameter of about 65 nm in the pressure pump pore analysis. The surface morphology is as follows: Figure 5 The wetting angle between the sealed alumina fiber reinforced alumina composite ceramic and water obtained in step 7 is 107°, and the thickness of the sealing layer is 28.2 μm. The alumina fiber reinforced alumina composite ceramic obtained in this embodiment meets the density requirements of the composite material, has good compressive resistance, and the surface sealing is successful.
[0093] Example 5: The preparation and surface sealing method of the graphene-enhanced alumina composite ceramic in this example is achieved by the following steps:
[0094] 1. A small-size alumina powder with a particle size of 200 nm and a large-size alumina powder with a particle size of 600 nm were mixed in a mass ratio of 92:8, and then graphene with a mass fraction of 1.4 wt% of the alumina mixed powder was added, and finally anhydrous ethanol was added to perform ball milling in an argon atmosphere, and a mixed powder was obtained after drying;
[0095] 2. dry pressing the mixed powder to obtain a green body;
[0096] 3. Sintering the green body at a temperature of 1200° C. in an argon atmosphere for 2 hours to obtain a graphene-enhanced alumina composite ceramic, hereinafter referred to as composite ceramic;
[0097] 4. Mixing the nano-alumina sol (the alumina particle size in the sol is 50 nm and the mass fraction is 15 wt%) with the external alumina powder with a particle size of 200 nm to obtain a mixed slurry;
[0098] 5. Immersing the composite ceramic into the mixed slurry for vacuum impregnation treatment to obtain the impregnated composite ceramic;
[0099] 6. Drying the impregnated composite ceramic at 60° C. for 12 hours to obtain a dried composite ceramic;
[0100] 7. Heat treating the dried composite ceramic at a temperature of 1200° C. for 2 hours to complete the sealed composite ceramic;
[0101] The mass fraction of the nano-alumina sol in the mixed slurry in step 4 is 94wt%, and the mass fraction of the added alumina powder is 6wt%.
[0102] The graphene-enhanced alumina composite ceramic obtained in step 3 of this embodiment has a density of about 75%, a compressive strength of 648 MPa, a wetting angle with water of 70°, and a pore diameter of about 65 nm in the pressure pump pore analysis. The surface morphology is as follows: Figure 6 The wetting angle between the sealed graphene-enhanced alumina composite ceramic and water obtained in step 7 is 106°, and the thickness of the sealing layer is 20.3 μm. The graphene-enhanced alumina composite ceramic obtained in this embodiment meets the density requirements of the composite material, has good compressive resistance, successful surface sealing, and good hydrophobicity.
[0103] Comparative Example: The preparation method of the porous alumina ceramics in this example is implemented according to the following steps:
[0104] (1) adding a small-particle alumina powder with a particle size of 200 nm to an appropriate amount of ethanol and wet-milling to obtain a uniform powder;
[0105] (2) filtering the uniform powder to obtain a green body;
[0106] (3) The green body was sintered at 1200°C for 2 hours to obtain a porous alumina matrix.
[0107] The density of the porous alumina matrix obtained in this comparative example is 84%, which exceeds the density range of 70%-80% required for the porous matrix of the composite material. Figure 7 shown.
Claims
1. A method for preparing porous alumina ceramics and sealing the surface of the ceramics, characterized in that This method is implemented by following the steps below:
1. Mixing a small-particle aluminum oxide powder having a particle size of 10-200 nm and a large-particle aluminum oxide powder having a particle size of 100-1000 nm in a mass ratio of (90-96):(4-10) to obtain a mixed powder; 2. Forming the mixed powder to obtain a green body; 3. Sintering the green body at a temperature of 1100-1250° C. for 2-6 hours to obtain a porous alumina matrix; 4. mixing the nano-alumina sol with the added alumina powder to obtain a mixed slurry; 5. Immersing the porous alumina substrate into the mixed slurry for vacuum impregnation treatment to obtain an impregnated alumina substrate; 6. Drying the impregnated alumina substrate to obtain a dried substrate; 7. Heat-treating the dried substrate at a temperature of 1100-1250° C. to complete the sealed alumina ceramic substrate; The mass fraction of the nano-alumina sol in the mixed slurry in step 4 is 90wt% to 95wt%, and the mass fraction of the added alumina powder is 5wt% to 10wt%.
2. The method for preparing and sealing the porous alumina ceramic according to claim 1, characterized in that The mixing method in step 1 is dry mixing or wet mixing.
3. The method for preparing and surface sealing porous alumina ceramics according to claim 1, characterized in that In step 1, a small-particle alumina powder with a particle size of 10-200 nm and a large-particle alumina powder with a particle size of 100-1000 nm are added in a mass ratio of (90-96): (4-10), and then graphene is added, and anhydrous ethanol is added to perform ball milling under an argon atmosphere, and a mixed powder is obtained after drying; wherein the graphene accounts for 1.2 to 2.0 wt% of the total mass of the small-particle alumina powder and the large-particle alumina powder.
4. The method for preparing and surface sealing porous alumina ceramics according to claim 1, characterized in that In step 2, the molding method is dry pressing molding or suction filtration molding.
5. The method for preparing and surface sealing porous alumina ceramics according to claim 1, characterized in that The preparation method of the green body is replaced by:
1. Mixing a small-size alumina powder with a particle size of 10-200 nm and a large-size alumina powder with a particle size of 100-1000 nm in a mass ratio of (90-96):(4-10), adding deionized water for wet ball milling to obtain an alumina slurry; 2. Inject the alumina slurry of step 1 into the stacked alumina fibers for vacuum impregnation, and then dry them to complete the grouting and impregnation treatment. Repeat the grouting and impregnation treatment multiple times to obtain a green body.
6. The method for preparing and surface sealing porous alumina ceramics according to claim 1, characterized in that In step 4, the alumina particle size in the nano alumina sol is 30-70 nm, and the mass fraction is 10wt%-30wt%.
7. The method for preparing and surface sealing porous alumina ceramics according to claim 1, characterized in that The particle size of the alumina powder added in step 4 is 10-200 nm.
8. The method for preparing and surface sealing porous alumina ceramics according to claim 1, characterized in that The heat treatment time in step seven is 2-6 hours.
9. The method for preparing and surface sealing porous alumina ceramics according to claim 1, characterized in that The sealed alumina ceramic substrate is subjected to a hydrophobic treatment.
10. The method for preparing and surface sealing porous alumina ceramics according to claim 9, characterized in that The hydrophobic treatment is to immerse the sealed alumina ceramic substrate in a methanol solution containing 1wt%-5wt% tridecafluorooctyltriethoxysilane for 1-4 hours and dry it in an oven at 100-200°C.
Citation Information
Patent Citations
Transparent lyophobic alumina film and preparation method thereof
CN101531469A
Vehicle exhaust purifier and preparation method thereof
CN105367112A
Monolithic base material and production method therefor
CN108883997A
Lightweight high-temperature-resistant interlayer thermal protection material and preparation method thereof
CN113563093A
Mixing process for preparing interlayer particle reinforced oxide ceramic-based composite material
CN114907103A